Long-term Results of the Side-to-side Isoperistaltic Strictureplasty in Crohn Disease: 25-year Follow-up and Outcomes. Issue 1 (July 2020) - Michelassi, Fabrizio; Mege, Diane; Rubin, Michele; Hurst, Roger D.
Abstract : Objective: Review the long-term outcomes of the side-to-side isoperistaltic strictureplasty (SSIS) and its effects on bowel preservation in Crohn disease (CD). Summary Background Data: The first SSIS was performed 25 years ago as an alternative to resection in the treatment of extensive fibrostenosing jejuno-ileal CD. Methods: Prospective study (January 1992–December 2016) of all patients with a SSIS performed by the authors. Long-term outcomes were evaluated radiographically, endoscopically, and histopathologically. Results: Sixty patients [14.4% of patients with jejuno-ileal bowel CD; 31 females; median age 36 (12–69) years] underwent 61 SSIS's for partial intestinal obstruction. Median length of preserved small bowel was 50 (20–148) cm. Associated strictureplasties and bowel resection were performed in 44% and 80%, respectively. Postoperative mortality occurred in 1 (PE on POD#8) and postoperative morbidity in 7 (12%). There were no sutureline dehiscences. SSIS resulted in resolution of preoperative symptoms in all. After a median follow-up of 11 years (range 1 mo–25 yrs), symptomatic recurrence was observed in 61%: 15 patients at the SSIS and 19 away from it (2 cases unclear location; 7 patients with >1 recurrence). Of 15 recurrences at SSIS's, 11 required surgical treatment (revision or strictureplasty in 6, SSIS removal in 5). Fifty-one patients (86%) maintain the original SSIS to date. Conclusions: SSIS is a safe, effective, and durable strictureplasty in patients with extensive fibrostenosing CD of the small bowel. Half the surgical recurrences on SSIS can be managed by subsequent revision or strictureplasty. The majority of patients maintain the original SSIS after a median follow-up of 11 years.